KosyFinder E-Commerce System Based on Web Geographic Information System and Expert System - Hardiana, Hardiana; Siaulhak, Siaulhak; Jumardi, Andi; Iriansa, Iriansa (Universitas Bumigora, 2024)
Background : The current problem of students and the community in searching for boarding house information only relies on information from friends, relatives or manual searches in searching for boarding house availability. Currently, the availability of information service provider platforms for boarding houses is now abundant, especially those based on websites or android-based. Boarding house information services based on websites or android-based only provide general information related to boarding house information, have not been able to provide comprehensive information. Objective : The purpose of this study is the KosyFinder e-commerce platform integrated with the Web Geographic Information System (WebGis) and Expert System which can help users in choosing a boarding as needed. Method : The research method used is Research and Development using the waterfall development model and the certainty factor (CF) method in diagnosing the health of the residential environment around the boarding house. Result : The results of this study were able to produce an e-commerce application product KosyFinder that was able to be integrated with WebGis and expert systems. The results of expert testing and user testing obtained a final value of 3.8 (very suitable), which means that the resulting system can be used. Conclusion : The platform that develops is functioning properly and as expected in accordance with the results of expert and user testing in the category is very appropriate.